The Role of Oxygen in Lithiation and Solid Electrolyte Interphase Formation Processes in Silicon-Based Anodes. Issue 12 (1st December 2022) - Li, Zhifei; Stetson, Caleb; Frisco, Sarah; Harvey, Steve; Huey, Zoey; Teeter, Glenn; Engtrakul, Chaiwat; Burrell, Anthony; Li, Xiaolin; Zakutayev, Andriy
Abstract : Silicon oxides (SiOx ) have been considered as promising alternatives to pure Si in high energy anodes in lithium-ion batteries (LIBs) due to their improved cycling stability. However, their fundamental lithiation mechanism has not yet been systematically investigated, and potential collateral downsides remain unclear. In this work, we report on the role of oxygen in lithiation/delithiation and solid electrolyte interphase (SEI) formation processes in SiOx thin film model electrodes with different oxygen contents. We show that the SiOx anodes with higher oxygen content experience smaller volume change and form a thinner and more stable SEI, both of which are beneficial for cycling stability. However, these SiOx anodes also show an irreversible lithiation at around 0.7 V attributed to the reduction of Si oxides, leading to lower first cycle coulombic efficiency that is undesirable for practical applications. Overall, these results offer a balanced perspective on the advantages and disadvantages that oxygen brings to Si-based anodes in LIBs.